Introduction to law & paralegal studies - Scuderi, Connie Farrell (McGraw-Hill, 2008)
Includes bibliographical references (p. 287-291) and index.; Scuderi’s Introduction to Law & Paralegal Studies teaches the basic skills paralegals will need when working in the field using pratical, uncomplicated approach. The material is directly applicable, providing an accurate sense of what paralegals do. The text provides basic coverage of the topics most important for a beginning paralegal student.